Women divided : gender, religion, and politics in Northern Ireland - Sales, Rosemary, 1947- (International studies of women and place., 1997)
Discussing both historical developments and contemporary events Women Divided offers topical and important new persectives on issues of gender and secterianism in Northern Ireland.